2023
DOI: 10.3390/land12071425
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of High-Quality Tourism Destinations Based on Spatiotemporal Big Data—A Case Study of Urumqi

Abstract: Although high-quality tourism destinations directly determine the tourism experiences of tourists and the management focuses of tourism management departments, existing studies have paid little attention to the relationship between tourism destinations of differing quality and tourist experiences. This study analyzed the spatiotemporal distribution of tourists and the quality of tourism destinations in Urumqi based on Tencent migration big data and Weibo sign-in big data and ultimately determined whether there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…With significant advantages in economic activities and resource allocation, a central city exerts a certain driving force on its peripheral cities and the entire regional economy. This effect is manifested as a greater degree of urbanization and more development opportunities as the distance from the central city decreases, as seen in the distribution of HH clustering in places like Dali and Lijiang [61]. However, previous studies have also found that the development brought about by the central city may have a certain impact on the preservation of traditional cultural heritage.…”
Section: Spatial Correlation Analysismentioning
confidence: 97%
“…With significant advantages in economic activities and resource allocation, a central city exerts a certain driving force on its peripheral cities and the entire regional economy. This effect is manifested as a greater degree of urbanization and more development opportunities as the distance from the central city decreases, as seen in the distribution of HH clustering in places like Dali and Lijiang [61]. However, previous studies have also found that the development brought about by the central city may have a certain impact on the preservation of traditional cultural heritage.…”
Section: Spatial Correlation Analysismentioning
confidence: 97%
“…The image holds a crucial position for destination marketers in distinguishing their destination within the context of the intense competition in the market [58]. Destination attributes summate to a brief description of a destination's fundamental characteristics, including the destination's image [59].…”
Section: Destination Imagementioning
confidence: 99%
“…Weibo sign-in data refer to the information generated by users' sign-in activities on Sina Weibo, documenting the specific locations and related details of user sign-ins. Compared to data from other social platforms, Sina Weibo sign-in data are characterized by their real-time nature and spatiotemporal attributes, capturing the timing and geographical location information of user sign-ins at various places [39]. In this study, we access the Sina Weibo open platform to acquire Weibo sign-in data for the year 2022, totaling approximately 10.34 million entries.…”
Section: Weibo Sign-in Datamentioning
confidence: 99%